Magnitude and determinants of unmet need for family planning among reproductive age women in East Africa: multilevel analysis of recent demographic and health survey data - Melsew Setegn Alie; Gossa Fetene Abebe; Yilkal Negesse (BMC, 2022)
Abstract Introduction Unmet need for family planning is the main obstacle to achieve healthy timing and desired number of children. Decreasing the unmet need for FP respects and protects human right and help to decrease the influence on biodiversity. Unmet need for family planning is the contributor and devastating issue of maternal health. Therefore, meeting the unmet need of contraceptive averts the maternal death and poverty. Therefore, determining the magnitude and its determinants is very important to intervene and design appropriate program umbrella. Objective To determine the magnitude and its determinants of unmet need for family planning among reproductive age women in East Africa. Method This study was analyzed secondary data from Demographic and Health Surveys (DHS) of which contained detailed family planning for all interviewed women aged 15 to 49 years. The data were weighted using sampling weight before any statistical analysis to account the sampling design. STATA version 15 was used for extracting, editing, recoding, and multilevel analysis. Median odds ratio (MOR), proportional change in Variance (PCV), Intraclass correlation coefficient (ICC), and Akaike Information Criteria (AIC) was analyzed. Four model was build and the best model was selected based on the smallest Akaike Information Criteria (AIC). Both bivariable and multivariable multilevel analysis was done. Variable with p-value< 0.25 were selected for multivariable multilevel logistic regression analysis. Variables with p-value ≤5% declared as statistical significant with outcome variable. Results The magnitude of unmet need for family planning was 24.66% (95%CI: 24.1-25.2). The identified determinants of unmet need for family planning was 30-39 years (AOR = 0.7; 95% CI 0.54-0.91), age of 40-49 (AOR = 0.76; 95% CI 0.58-0.99), rural residence (AOR = 1.17; 95% CI 1.02-1.34), female household head (AOR = 0.66; 95% CI 0.61-0.73), women having 4-6 child (AOR = 1.76; 95% CI 1.55-1.99), women having 7-9 child (AOR = 2.77; 95% CI 2.34-3.28) women having ≥10 child (AOR = 3.51; 95% CI 2.58-4.78), women who give their first birth 19-25 years (AOR = 1.1; 95% CI 1.0-1.26), 26-34 years (AOR = 1.4; 95% CI 1.19-1.83) ≥35 years (AOR = 2.1; 95% CI 1.1-4.27) and no fertility desire (AOR = 1.52; 95% CI 1.36-1.67) were the determinants of unmet need for family planning in east Africa. Conclusion Unmet need in east Africa is high as compare to other previous study. Maternal age, residence, sex of household head, number of children, age at first birth and fertility desire were the determinants identified in this study. Therefore, health interventions that reduce unmet need which enhance family planning service delivery among rural, male-headed household, women having more than three children and women who had no fertility desire needed in advance. Policies and programs of unmet need should be tailored the rural, young and no fertility desire women as well as male headed households.